Do Antiepileptic Drugs Change the Levels of Arginine Derivatives in Epileptic Children Treated with Polytherapy? The Results of a Case–Control Study - Beata Sarecka-Hujar; Izabela Szołtysek-Bołdys; Ilona Kopyta (Children, 2022)
Previously, a relation between therapy with antiepileptic drugs (AEDs) and the levels of biochemical parameters was observed in adult patients suffering from epilepsy. Among these biochemical factors, arginine derivatives are often analyzed, i.e., asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), and homoarginine (hArg) as they may be linked with increased risk for cardiovascular disease (CVD). Since the levels of arginine derivatives may increase during therapy, and the treatment of epilepsy often lasts many years, patients may experience CVD faster. The aim of the present study was to analyze the levels of arginine derivatives in children with epilepsy who were treated with multiple AEDs to answer the question whether pediatric patients may be at increased risk of CVD in the future. We prospectively analyzed 21 children suffering from epilepsy who took ≥2 AEDs for at least 6 months and 22 children without epilepsy (reference group). The levels of the arginine derivatives, e.g., ADMA, SDMA, and hArg, were determined in the blood serum using the HPLC method. No differences in both the mean levels of ADMA and SDMA, as well as in the mean values of the arginine derivative ratios, were observed between the groups. The tendency toward a lower level of hArg was found in epileptic patients more than in the reference group (p = 0.091). Epileptic children receiving three or more AEDs had significantly lower concentrations of hArg and values of the hArg/ADMA ratio than the reference group (p = 0.023 and p = 0.006, respectively). In turn, the mean hArg/ADMA ratio was lower in children receiving three or more AEDs compared to children receiving two AEDs (p = 0.002). There was also a positive correlation between the hArg and ADMA concentrations in children with epilepsy taking two AEDs; the higher the level of hArg, the greater the level of ADMA on average (r = 0.650, p = 0.022). Taking three or more AEDs by epileptic children resulted in lower levels of both hArg and the value of the hArg/ADMA ratio.